Ambient UVA‐Induced Expression of p53 and Apoptosis in Human Skin Melanoma A375 Cell Line by Quinine. (15th March 2013) - Yadav, Neera; Dwivedi, Ashish; Mujtaba, Syed Faiz; Kushwaha, Hari Narayan; Singh, Shio Kumar; Ray, Ratan Singh
Abstract This study aimed to analyze the phototoxic mechanism and photostability of quinine in human skin cell line A375 under ambient intensities of UVA (320–400 nm). Photosensitized quinine produced a photoproduct 6‐methoxy‐quinoline‐4‐ylmethyl‐oxonium identified through LC‐MS/MS. Generation of 1O2, O2−, and OH was measured and further substantiated through their respective quenchers. Photosensitized Quinine (Q) caused degradation of 2‐deoxyguanosine, the most sensitive nucleotide to UV radiation. The intracellular ROS was increased in a concentration‐dependent manner. Significant reduction in metabolic status measured in terms of cell viability (54%) at 25 μg mL−1 was observed through MTT assay. Results of MTT assay accord NRU assay. Single strand DNA breaks and apoptosis were increased significantly (P < 0.01) as observed through comet assay and EB/AO double staining. Photosensitized quinine caused cells to arrest in G2 phase of cell cycle and induced apoptosis (5.08%) as revealed through FACS. Real‐Time PCR showed upregulation of p21 (4.56 folds) and p53 (2.811 folds) genes expression. Thus, our study suggests that generation of reactive oxygen species by quinine under ambient intensity of UVA may result into deleterious phototoxic effects among human population.